Gait Analysis in Rats with Single Joint Inflammation: Influence of Experimental Factors - Ängeby Möller, Kristina; Kinert, Susanne; Størkson, Rolf; Berge, Odd-Geir (PLOS ONE, 2012)
Disability and movement-related pain are major symptoms of joint disease, motivating the development of methods to quantify motor behaviour in rodent joint pain models. We used observational scoring and automated methods to compare weight bearing during locomotion and during standing after single joint inflammation induced by Freund's complete adjuvant (0.12–8.0 mg/mL) or carrageenan (0.47–30 mg/mL). Automated gait analysis was based on video capture of prints generated by light projected into the long edge of the floor of a walkway, producing an illuminated image of the contact area of each paw with light intensity reflecting the contact pressure. Weight bearing was calculated as an area-integrated paw pressure, that is, the light intensity of all pixels activated during the contact phase of a paw placement. Automated static weight bearing was measured with the Incapacitance tester. Pharmacological sensitivity of weight-bearing during locomotion was tested in carrageenan-induced monoarthritis by administration of the commonly used analgesics diclofenac, ibuprofen, and naproxen, as well as oxycodone and paracetamol. Observational scoring and automated quantification yielded similar results. We found that the window between control rats and monoarthritic rats was greater during locomotion. The response was more pronounced for inflammation in the ankle as compared to the knee, suggesting a methodological advantage of using this injection site. The effects of both Freund's complete adjuvant and carrageenan were concentration related, but Freund's incomplete adjuvant was found to be as effective as lower, commonly used concentrations of the complete adjuvant. The results show that gait analysis can be an effective method to quantify behavioural effects of single joint inflammation in the rat, sensitive to analgesic treatment.